The Role of Attitude and Skills in Entrepreneurial Human Capital: Evidence from a Systematic Literature Review - Afando Ekardo; Yunia Wardi; , Hendrik Heri Sandi; Susi Evanita (Journal Development Manecos, 2026)
Entrepreneurial human capital has increasingly been recognized as a critical determinant of entrepreneurial success, innovation, and business sustainability. While previous studies have extensively examined entrepreneurial attitude and entrepreneurial skills, these dimensions have often been investigated separately, resulting in fragmented understanding of how they collectively contribute to entrepreneurial human capital. This study aims to synthesize existing empirical evidence on the roles of entrepreneurial attitude and entrepreneurial skills and to examine their integration within the entrepreneurial human capital framework. A systematic literature review (SLR) was conducted following the PRISMA guidelines. Relevant studies published between 2000 and 2025 were identified through searches in Scopus, Web of Science, ScienceDirect, and SpringerLink using structured Boolean search strings. After applying predefined inclusion, exclusion, and quality assessment criteria, eligible empirical studies were analyzed through thematic synthesis. The findings reveal that entrepreneurial attitude functions as a motivational resource that influences entrepreneurial intention, opportunity recognition, persistence, and the willingness to invest in entrepreneurial learning. Entrepreneurial skills, including opportunity recognition, decision-making, leadership, networking, and risk management, provide the operational capabilities required to transform entrepreneurial intentions into effective entrepreneurial actions. More importantly, the review demonstrates that entrepreneurial attitude and entrepreneurial skills are complementary dimensions whose interaction forms a stronger and more comprehensive entrepreneurial human capital than either dimension alone. This study contributes to entrepreneurship literature by proposing a multidimensional conceptualization of entrepreneurial human capital that integrates motivational and competency-based resources. The findings also highlight the importance of entrepreneurship education and training programs that simultaneously foster positive entrepreneurial attitudes and practical entrepreneurial competencies to enhance entrepreneurial performance and sustainable venture success.